2007
DOI: 10.1002/gps.1708
|View full text |Cite
|
Sign up to set email alerts
|

Personal identification (PIN) numbers: a new cause of financial exclusion in older people

Abstract: Since April 2003 the UK government has been phasing out paper pension books. Previously, many older people received their pension benefits by using paper slips which were exchanged for cash at the Post Office. Now, the state pension is transferred directly into a bank account and cash obtained by using a bank card, keypad and a four digit personal identification (PIN) number. The system is believed to be more secure and mirrors wider changes in the UK retail sector. People with dementia or early memory problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…They might also voluntarily exclude themselves from the financial market due to their poor understanding of the benefits associated with owning financial products and/or because they do not know that the financial product exists (Cnaan et al , 2012). For example, Sampson et al (2007) found that older people in the UK were more susceptible to financial exclusion once the government began to directly transfer pensions to online bank accounts, as older people were more likely to encounter difficulties navigating the keypad system and remembering their four-digit personal identification number. To engage in the financial market, individuals thus need to be able to fully understand mainstream offerings as well as their benefits.…”
Section: The Role Of the Individual: Social Exclusion And Financial Cmentioning
confidence: 99%
“…They might also voluntarily exclude themselves from the financial market due to their poor understanding of the benefits associated with owning financial products and/or because they do not know that the financial product exists (Cnaan et al , 2012). For example, Sampson et al (2007) found that older people in the UK were more susceptible to financial exclusion once the government began to directly transfer pensions to online bank accounts, as older people were more likely to encounter difficulties navigating the keypad system and remembering their four-digit personal identification number. To engage in the financial market, individuals thus need to be able to fully understand mainstream offerings as well as their benefits.…”
Section: The Role Of the Individual: Social Exclusion And Financial Cmentioning
confidence: 99%